Penerapan Standar Akuntansi Keuangan Nomor 16 Mengenai Aset Tetap pada Rumah Sakit di Indonesia: Sebuah Studi Literatur - Maya Widiastri (Journal of Current Research in Management, Policy, and Social Studies, 2024)
This study aims to examine the application of Financial Accounting Standards (PSAK) 16 in hospitals to present transparent and accurate financial reports. The method used by the researcher is a Literature Review (LR). This study utilizes data from journals available in full-text format. The results of the research indicate that the reporting of fixed assets in hospitals in Indonesia does not yet comply with PSAK 16. Therefore, training and improvement of management and hospital staff’s understanding of PSAK 16 are necessary to produce financial reports that are transparent and accurate, in line with applicable standards, and contribute to the accounting literature in the healthcare sector.